Modernizing landscape design extension resource - Luan, Jianqiao (Kansas State University, 2018)
Kansas State University Research and Extension is an educational network sharing unbiased, research-based information and expertise with Kansas residents. To improve quality of life, residential landscape design is an important educational topic for homeowners. The objective of this project is to update a Kansas State University Research and Extension Publication, Residential Landscape Design (publication number: S-4), which was published in 1980. Content, text and graphics need to be updated to address contemporary learner needs. An updated resource also needs to display a modern aesthetic, since the original graphics were created almost four decades ago. In order to understand the process and experience of updating an educational landscape design resource, similar publications from other land-grant universities were reviewed. This study discusses, compares, and contrasts the contents, range of page numbers, graphic styles, color, publication versions, and publication date among other similar types of university Extension publications.
Keywords: Landscape design; Extension publication